What makes a hero - Bobowicz, Pamela; Kaban, Eda (Los Angeles : Marvel, 2019)
The heroes in the Marvel Cinematic Universe are here to answer one vital question: What makes a hero? Whether they're fighting evil throughout the realms or defending humanity on Earth, these heroes have their own approaches to strength, goodness, and heroism. Join these women as they explore what it means to be a hero. Where we find real strength, and how to find your very own super-power.
3.5
K-3
Keywords: Women superheroes -- Juvenile fiction; Superheroes -- Juvenile fiction; Women superheroes -- Fiction; Superheroes -- Fiction; Illustrated works